Effectiveness of the GRACE risk score according to troponin elevation in patients admitted with non-ST elevation acute coronary syndrome: a post hoc analysis of the UKGRIS parallel group cluster randomised controlled trial - Chris P Gale; Derek P Chew; Andrew T Yan; David B Brieger; Ramesh Nadarajah; Catherine Reynolds; Catherine Fernandez; Linda Sharples; Kathryn Carruthers; Keith A A Fox; Rachael Gilberts; Shaun Goodman; et al. (Open Heart, 2025)
Background The effectiveness of risk stratification using the Global Registry of Acute Coronary Events (GRACE) Risk Score (GRS) for patients presenting to hospital with suspected non-ST elevation acute coronary syndrome (NSTEACS) according to troponin elevation is unknown.Methods Post hoc analysis of a phase 3 parallel group cluster randomised controlled trial (UK GRACE Risk Score, UKGRIS) of adult patients presenting with suspected NSTEACS to 42 hospitals in England between 9 March 2017 and 30 December 2019, with hospitals randomised (1:1) to standard care or according to the GRS and associated guidelines. Coprimary outcome measures were use of guideline-recommended management and time to the composite of cardiovascular death, non-fatal myocardial infarction, new-onset heart failure hospitalisation or readmission for cardiovascular event at a minimum of 24 months follow-up.Results A total of 3050 patients were randomised in UKGRIS, of whom 2602 had troponin elevation. The relative effect of GRS compared with standard care on the uptake of guideline-recommended care was greater for participants with troponin elevation compared with those without (relative OR 1.52, 95% CI 1.16 to 2.00, p<0.01). The time to the first composite event was not improved by the GRS among participants with (HR 0.89, 95% CI 0.70 to 1.14) or without troponin elevation (HR 1.14, 95% CI 0.79 to 1.64), with no interaction (relative HR 0.79, 95% CI 0.57 to 1.08, p=0.14 for interaction).Conclusions For suspected NSTEACS, the effect of the GRS compared with standard care on uptake of recommended processes in those with elevated troponin was higher than in those without. However, this did not translate into a reduction in the composite primary or secondary outcomes at 24 months.Trial registration number ISRCTN29731761.